New Records of Snakes (Reptilia, Squamata, Serpentes) Distribution in Lai Chau Province,Vietnam - Anh, Pham Van; Truong, Nguyen Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 1DO - 10.25073/2588-1140/vnunst.4854, 2019)
The 2017-2018 survey of the herpetological in Sin Ho forest (Lai Chau province) identified five new snake species, namely Dendrelaphis pictus (Colubridae), Bungarus multicinctus (Elapidae), Hebius chapaensis (Natricidae), Pareas carinatus (Pareatidae), and Ovophis monticola (Viperidae). The findings raised the total number of the snake species recorded in Lai Chau province to 26. The paper also provides additional information on the morphology and habitat of the above-named species. Keywords New records, Colubridae, Elapidae, Natricidae, Pareatidae, Viperidae. References [1] Ủy Ban nhân tỉnh Lai Châu, Công thông tin điện tử. http://http://sinho.laichau.gov.vn, 2018 (cập nhật ngày 6 tháng 1 năm 2019). [2] S.V. Nguyen, C.T. Ho, T.Q. Nguyen, Herpetofauna of Vietnam. Edition Chimaira, Frankfurt am Main, 2009. [3] T. Ziegler, H.N. Ngo, A.V. Pham, T.T. Nguyen, M.D. Le, T.Q. Nguyen, A new species of Parafimbrios from northern Vietnam (Squamata: Xenodermatidae), Zootaxa 4527(2) (2018) 269-276. http://dx.doi.org/10.11646/zootaxa 4527.2.7. [4] R. Bourret, Les serpents de l'Indochine. H. Dasuyau, Toulouse, 1936. [5] M.A. Smith, The fauna of Bistish india, Ceylon and Burma, reptilia and Amphibia. Vol III. Serpentes, 1943. [6] T. Ziegler, G. Vogel, On the knowledge and specific status of Dendrelaphis ngansonensis (Bourret, 1935) (Reptilia: Serpentes: Colubridae), Russian Journal of Herpetology. 6(3) (1999) 199-208. [7] Nguyễn Văn Sáng, Động vật chí Việt Nam (Phân bộ Rắn), Tập 4, Nxb Khoa học và Kỹ thuật, Hà Nội, 2007. [8] Phạm Văn Anh, Nguyễn Thị Bích Ngọc, Nguyễn Thị Mến, Nguyễn Lân Hùng Sơn, Nguyễn Quảng Trường, Ghi nhận mới về sự phân bố của một số loài rắn (Squamata: Serpentes) ở tỉnh Sơn La, Báo cáo khoa học, Kỷ yếu hội nghị toàn quốc về Sinh thái và Tài nguyên sinh vật lần thứ 5 (2013) 461-467. [9] J.L. Ren, K. Wang, T.T. Nguyen, C.V. Hoang, G.H. Zhong, K. Jiang, P. Guo, J-T. Li, Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China, Zootaxa 4486. (1) (2018) 031-056. [10] R. Bourret, Notes herpétologiques sur l'Indochine Française I. Ophidiens de Chapa. Bull. Gen. Instr. Pub. Hanoi 7 (March 1934) 129-138. [11] K. Guo, D. Xuejiang, A new species of Pareas (Serpentes: Colubridae: Pareatinae) from the Gaoligong Mountains, southwestern China, Zootaxa. 2008 (2009) 53-60. [12] A. Malhotra, K. Dawson, P. Guo, S.R. Thorpe, Phylogenetic structure and species boundaries in the mountain pitviper Ovophis monticola (Serpentes: Viperidae: Crotalinae) in Asia, Molecular Phylogenetics and Evolution. 59 (2) (2011) 444-457.